Fractals via Generalized Jungck–S Iterative Scheme - Zhihua Chen; Muhammad Tanveer; Waqas Nazeer; Jing Wu (Discrete Dynamics in Nature and Society)
The purpose of this research is to introduce a Jungck–S iterative method with m,h1,h2–convexity and hence unify different comparable iterative schemes existing in the literature. A Jungck–S orbit is constructed, and escape radius is derived with our scheme. A new escape radius is also obtained for generating the fractals. Julia and Mandelbrot set are visualized with the help of proposed algorithms based on our iterative scheme. Moreover, we present some complex graphs of Julia and Mandelbrot sets using the derived orbit and discuss their nature in detail.